POTENSI SENYAWA FLAVONOID DAUN AFRIKA (Vernonia amygdalina Del.) ASAL TERNATE SEBAGAI ANTIOKSIDAN - Sukmawati Sukmawati; Harira Hadi; Aminah Aminah (As-Syifaa Jurnal Farmasi, 2017)
African Leaf (Vernonia amygdalina Del.) belonging Asteraceae family. The African leaf contain flavonoids, alkaloids, saponins, terpenoids, tannins, glycosides, indole alkaloids, anthraquinones and luteolin. This study aimed to measure the potencyl of flavonoid compounds of African leaf (Vernonia amygdalina Del.) origin Ternate using DPPH and FRAP. Extraction by maceration method using ethanol 96%. The compounds identification in African leaf extract contains flavonoids. The absorbance was measured at the maximum wavelength of 515 nm. DPPH scavenging showed that ethanol extract has weak antioxidant activity based on AAI 0.454 value. This potency is lower in comparasion with quersetin which has a value of AAI 6,315 and for FRAP methods, the absorbance was measured at the wavelength of 720 nm with the antioxidant capacity is 14,846 mgQE / gram.